The use of electronically mediated authentic pictures to aid composition writing: a study on a group of primary 4 ESL pupils at Sk Laksamana / Alban @ William John Lisen - John Lisen, Alban @ William (2004)
Since the introduction of modem technology into the field of language teaching, every language teacher is aware of enormous variety of authentic materials that are available at their disposal. Teachers need to apply their creative thought and constantly be on the lookout for the new ideas and devise authentically usable materials for the ESL classroom. One of these time-tested methods is the use of stimulating pictorial or graphical elements to aids teaching and learning “The Curriculum Specification for the English language syllabus for primary schools has outlined separate documents called ‘Hurian Sukatan Pelajaran’. These documents help the teacher to focus on the skills that need to be taught, the content or the topics that should be dealt with and the vocabulary and grammar items that the pupils must know for their learning of the language. Pupils are taught the different purpose and the functions of written language, serve as a means of remembering, communicating, organizing and developing ideas and information, and as a source of enjoyment” (Guided Writing Exercise for Primary School - a Workshop Product, Bahagian Kurikulum Jabatan Pendidikan Sarawak, Kuching). They should be taught to identify the purpose for which they write and to write for a range of readers, e.g. their teacher, friends, family members etc. Pupils should be taught to write in a range of forms (text types) or genres incorporating some of different characteristics of these forms (e.g. lists, captions); observations; and messages, notes invitations, instructions, etc. They should be able to write independently but when this is not possible, teachers must set guided writing